Electrophiles and Michael acceptors as Nrf2 modulators in a Caenorhabditis elegans model. - Lee , Chong Yew
Amyloid-beta (AI3) toxicity has been proposed and demonstrated to be a key contributor to the neurodegenerative process in the pathogenesis of neurodegenerative diseases such as Alzheimer's disease (AD).The mechanisms by which AI3 leads to neuronal damage and dysfunction are still not well understood.